Multicultural Approach to Education - Koriakina, Anzhelina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article discusses the definition of a multicultural approach to education. The views of foreign and Russian researchers on this problem are represented. Features of a multicultural approach - dialogue of cultures in historical and contemporary context, cultural pluralism, multi-ethnicity – are showed. It is concluded that in Russia the term "multicultural approach to education" is used in the meaning "multi-ethnic".